Exploring attitudes toward aquaculture in Norway – Is there a difference between the Norwegian general public and local communities where the industry is established?. (October 2019) - Krøvel, A.V.; Gjerstad, B.; Skoland, K.; Lindland, K.M.; Hynes, S.; Ravagnan, E.
Abstract: In order to achieve sustainable growth of the aquaculture industry, factors such as environment, economy and public opinions need to be accounted for. In this paper, we explore and compare attitudes towards the aquaculture industry in a statistical representative sample of Norwegians with attitudes in a representative sample from a local area where the aquaculture is highly present, also in Norway. Analysis of the national and local samples allows for investigation of how opinions towards aquaculture vary according to both demographical variables and geographical setting. Our findings suggest that being from an area where the industry dominates does not give one a more negative view of the environmental threat of the industry, but does make one less likely to believe that aquaculture activity creates local employment. In addition, the results show that in a community where the aquaculture industry dominates, negative attitudes towards aquaculture are not primarily due to its perceived environmental impact, but rather due to conflicts of interest and to whether aquaculture activity is perceived to create jobs locally or not. Highlights: Aquaculture is not considered the most severe threat to the marine environment. Living in close proximity to aquaculture does not seem to make people more critical. Perceived environmental impact shape attitudes towards aquaculture in national sample. Perceived job creation shape attitudes to aquaculture in local sample. Perceived conflict shape attitudes in both local and national sample.